Introduction: Never Cuss the Rain - Christy Davis (Symphony in the Flint Hills, 2018)
Introduction: When I woke up to the sound of sleet hitting my roof, I knew that I’d have to change the day’s travel plans. By 7:00 a.m. I had a message from rancher Matt Perrier. At his Greenwood County ranch ice was darting across the open prairie in gusts up to fifty miles per hour.